Acute Toxicity of Earthworm (Pheretima javanica K.) Powder on Renal Histopathological Description of Rat (Rattus norvegicus B.) - Dwi Wahyuni; Joko Waluyo (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2017)
Earthworm (Pheretima javanica K.) is a common soil biofertilizer. This repulsive animal for some has been widely used for remedial medicine as well. Simplicia being used in this study was obtained from dried and blended earthworm along with its intact internal organs. The aim of the study was to determine the toxicity effect of earthworms powder to renal histopathology in rats (Rattus norvegicus). A total of 50 rats were divided into five groups consisting of a negative control group (2 ml 1% CMC Na), P1 earthworms group at dose of 0.4 grams, P2 earthworms groups at dose of 0.8 grams, P3 earthworms group at a dose of 1.6 grams, and P4 earthworms group at a dose of 3.2 grams. The rats were acclimated for about a week, then orally induced by earthworm powder. The treatments were conducted for 14 consecutive days to see any toxic symptoms developed. ANOVA results showed the administration of earthworm (Pheretima javanica K.) powder did not significantly affect renal physiology and histopathology. There was no damage observed microscopically. Keywords: Pheretima javanica K. powder, Rattus norvegicus B., renal histopathology.